THE MILITARY GLIDER REVISITED - Heitman, Helmoed-Römer (Scientia Militaria - South African Journal of Military Studies, 2012)
The military glider has, arguably, enjoyed the briefest life span of any major military equipment type - spanning not much more than a decade and a half from the entry into production of the first, to the demise of the concept as such. During its heyday, however, the glider was instrumental in not a few spectacular operations. Thus, it is not really surprising that some of the more iconoclastic military thinkers have, albeit infrequently, wondered whether there is not still a place for up to date gliders in modern warfare.